Effect of trees on colonization of intercrops by vesicular arbuscular rnycorrhizae in agroforestry systems - KUMAR, ANIL; SHUKLA, A; HASHMI, S; TEWARI, R K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted (during 2004-05) to access the effect of trees on colonization of intercrops by vesicular arbuscular mycorrhizae in agro forestry systems under and outside tree canopy in 43 tree crop combinations. Trees acted as vesicular arbuscular mycorrhizal inoculum reservoir for intercrops in most of the combinations. During rainy (kharif) season colonization index of intercrops was significantly more under tree canopy in all 24 tree-crop combinations as compared to respective values outside tree canopy. During winter (rabi) season colonization index of intercrops was significantly more under tree canopy only in 5 combinations, viz ber (Zizyphus rnauritiarla L.) + wheat (Triticurlz aestivum L. emend. Fiori & Paol), neem (Azadirachta indica A. Juss.) + wheat, neem + gram (Cicer arietinu~tl L.), neem + pea (Pisurn sativunz L.) and teak(Tectorzagrandis L.E) +gram, than outside tree canopy. The index of the intercrops was at par under and outside tree canopy in remaining 14 combinations. A net-house study under different shade levels showed that heavy shade reduced vesicular arbuscular mycorrhizal colonization in wheat when winter was at its peak. Results on effect of different shading conditions on microclimate of net house indicated that with increase in per cent shade, soil moisture increased and soil surface temperature, sub soil temperature at 10 cm depth and lux meter reading at 12 noon decreased.